ENANTIOMERIC SEPARATION OF LEVOFLOXACIN IN DRUG PRODUCT AND DRUG SUBSTANCE USING CHIRAL STATIONARY PHASE - K.PUSHPA LATHA,; D.RAMACHANDRAN, (International Journal of Pharma and Bio Sciences, 2013)
A chiral liquid chromatographic method was developed for the enantiomeric purity of Levofloxacin in drug substance as well as in drug product. The chromatographic separation was achieved on Chiralpak IC 150 X 2.1mm X 5μm, column using a mobile phase system consisting of n-hexane and isopropyl alcohol in the ratio of 95:5 (v/v). The mobile phase was pumped through column at the flow rate of 1 mL min-1. The resolution between the enantiomers was found to be more than three. The developed method was subsequently validated and proved to be accurate, specific and precise. The experimentally established limit of detection and quantification for (R)-enantiomer of Levofloxacin were found to be 0.509 μg mL-1 and 1.316 μg mL-1 respectively for 20 μl injection volumes. The percentage recovery of (R)-enantiomer was ranged between 95 to 105 % in drug product as well as in drug substance. The proposed method was found to be suitable and accurate for the quantitative determination of chiral purity of Levofloxacin in drugs substance as well as in drug product.